Relationship of physicians with the pharmaceutical industry in Pakistan: present status, issues, and way forward - Waris Qidwai (Journal of the Pakistan Medical Association, 2024)
This manuscript examines the ethics of the relationship between the pharmaceutical industry and practising physicians. The pharmaceutical industry is alleged to provide incentives to physicians and who in return are expected to prescribe their manufactured medications. Such practices are often considered unethical and against the rules and regulations of the regulatory bodies. The core issue facing physicians and pharmaceutical industry relationships is lack of regulation and accountability. Public education and awareness are lacking, and they are unable to question prescription practices of practicing physicians. Patient advocacy groups do not exist to safeguard the patient’s rights. There is a need to strengthen regulatory control to ensure the physician community and pharmaceutical industry relationship remains ethical. Both the physician community and pharmaceutical industry are important stakeholders in healthcare delivery and the ethical relationship between them will benefit health care services. Further discussion and debate on this important yet extremely sensitive issue is strongly recommended. Keywords: Physicians; Pharmaceutical industry; Ethics; Regulatory body; Monitoring